PERENCANAAN EMBUNG BLORONG KABUPATEN KENDAL, JAWA TENGAH - Muhammad Erri Kurniawan; Yudha Satria; Sugiyanto Sugiyanto; Hary Budieny (Jurnal Karya Teknik Sipil, 2014)
Blorong small dam situated on the Blorong River, Kendal Regency. Blorong small dam is planned to meet the requirement of water in Kedung Pengilon irrigation area experiencing water shortages during the dry season, the months of September and October. Area has experienced drought during the dry season is expected around 1200 Ha. Discharge mainstay Blorong River calculated based FJ. Mock method with the possibility of not being met by 20%. Small dam reservoir volume is 1,589,705.56 m3 which is at an elevation of +39,00 to +53,00. Results of water balance calculations indicate that in September and October there is a shortage of water, each for 1.253.648 m3 and 122.758 m3. Flood discharge plan obtained from HSS Gama I method is equal to 503.7558 m3/s return period of 25 years (Q25 = 503.7558 m3/s). The planned small dam 19 m high, with a base elevation ponds +39.00, +58.00 dam crest elevation, surveillance 2.00 m high, 7.00 m wide dam crest, upstream slope of 1:2,5, 1:1,75 downstream slope. In planning this Blorong small dam used ogee type spillway width 30.00 m with a height of 14 m and a spillway crest elevation of +53.00, using an eject USBR Type IV with a length of 15.70 m. This project implementation is scheduled for 35 weeks with a budget plan  of Rp 24.242.419.000,00.